Efektifitas Mind Mapping Dalam Pembelajaran Kosakata Bahasa Jepang Pada Pemelajar Tingkat Dasar - Rosita Ningrum (Lingua Cultura, 2012)
Article clarified the research entitled 「「初級学習者における日本語の語彙学習においてのマイ ンド・マッピングの効果」which were translated as "The Effectiveness of Mind Mapping In JapaneseVocabulary Learning for A Basic Level Learners". In previous studies, mind mapping was tested on reading skill, but for this research it was focused on vocabulary with the assumption that the language learners usually got difficulties in learning both languages. Technique of mind mapping was tested on a two-semester student to find out the effectiveness of its techniques in learning Japanese vocabulary. This research used experimental methods. This design involved two groups of subjects. One group, as experimental group, was given the mind mapping learning technique, and the other group (the control group) was treated with the conventional learning techniques. Data were taken in two ways, the quantitative method was using instrument in the forms of pre test and post test on both sample class. The qualitative method applied interview to complete the descriptive data analysis. Then, the pre test and post test data were analyzed by measuring the normality of data and test-t to know to what extent the effectiveness of mind mapping techniques was successfully applied to the sample. To strengthen those results, the outcomes of interview was transcribed to see the sample’s responses in line with mind mapping techniques to the study of Japanese vocabulary. The research result indicates that mind mapping technique is proven more effective in learning Japanese vocabulary compared to the conventional way.